2021
DOI: 10.3390/ani11072133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multivalent BRD Vaccine Treatment and Temperament on Performance and Feeding Behavior Responses to a BVDV1b Challenge in Beef Steers

Abstract: This study examined the effects of multivalent respiratory vaccine treatment (VT) and animal temperament classification on feeding behavior traits, feed intake and animal performance in response to a bovine viral diarrhea virus (BVDV) challenge. Nellore–Angus crossbred steers (n = 360; initial body weight (BW) 330 ± 48 kg) were assigned to one of three vaccine treatments: non-vaccinated (NON), modified live (MLV) and killed (KV) regarding respiratory viral pathogens, and inoculated intranasally with the same B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
2
Order By: Relevance
“…As the RES steers had 22% lower (P = 0.05) serum cortisol concentrations than NON steers both prior to and following inoculation, we posit that the relatively slower eating rates exhibited both prior to and following the MH challenge are due to the RES steers having more calm temperaments than NON steers. Cattle with calm temperaments have been reported to have lesser basal cortisol concentrations than cattle with excitable temperaments (Curley et al, 2006;Burdick et al, 2011), and have greater DMI, longer bunk visit duration, and slower eating rate (Smith et al, 2017;Olson et al, 2019). Although RES steers had reduced serum cortisol and bunk visit eating rate prior to inoculation which suggests a calmer temperament, a single-point measure of prestudy exit velocity was not affected by HPT classification (data not shown).…”
Section: Performance and Feeding Of Pre-and Postchallenge Periodsmentioning
confidence: 88%
“…As the RES steers had 22% lower (P = 0.05) serum cortisol concentrations than NON steers both prior to and following inoculation, we posit that the relatively slower eating rates exhibited both prior to and following the MH challenge are due to the RES steers having more calm temperaments than NON steers. Cattle with calm temperaments have been reported to have lesser basal cortisol concentrations than cattle with excitable temperaments (Curley et al, 2006;Burdick et al, 2011), and have greater DMI, longer bunk visit duration, and slower eating rate (Smith et al, 2017;Olson et al, 2019). Although RES steers had reduced serum cortisol and bunk visit eating rate prior to inoculation which suggests a calmer temperament, a single-point measure of prestudy exit velocity was not affected by HPT classification (data not shown).…”
Section: Performance and Feeding Of Pre-and Postchallenge Periodsmentioning
confidence: 88%
“…Аналіз останніх досліджень і публікацій. Дослідженню особливостей застосування сучасного цифрового інструментарію в діяльності підприємств тваринництва присвячено роботи багатьох дослідників, серед яких: Alonso R. S., Sittón-Candanedo I., García O., Prieto J., Rodríguez-González S., Canga D., Boğa M., Fuentes S., Viejo C., Cullen B., Tongson E., Chauhan S., Dunshea F. R., Kakani V., Nguyen V. H., Kumar B. P., Kim H., Pasupuleti V. R., Smith P., Carstens G., Runyan C., Ridpath J., Sawyer J., You J., Lou E., Afrouziyeh M., Zukiwsky N. M., Zuidhof M. J., Болтянська Н., Подашевська Н., Скляр О., Скляр Р., Болтянський О. та інші [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
unclassified
“…При цьому ці прилади не тільки дуже специфічні і чутливі до аналізованих параметрів, вони надійні і прості у використанні, а також прискорюють процес моніторингу. Нові біосенсори для управління тваринництвом надають значні переваги в моніторингу фізіологічного здоров'я тварин шляхом виявлення та ізоляції хвороб, моніторингу здоров'я та виявлення циклів розмноження, а також додатково аналізу навколишнього середовища тварини [2]. Очікується, що дані, отримані в результаті моніторингу інтегрованого тваринництва, в майбутньому допоможуть фермерам та сільськогосподарській галузі підвищити продуктивність тварин.…”
unclassified